2014
DOI: 10.1159/000363340
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Superoxide Dismutase Gene Expression and Cognitive Functions in Recurrent Depressive Disorder

Abstract: Background: Recent studies have revealed that recurrent depressive disorders (rDD) are linked with dysregulation of the immune system. Previous studies have found that manganese superoxide dismutase (MnSOD, SOD2) may be a key inflammatory enzyme involved in this disorder. The purpose of this study was to determine the mRNA and protein levels of MnSOD in patients with rDD and to define the relationship between serum MnSOD levels and cognitive performance. Methods: The study comprised 236 subjects, which include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Reduced levels of antioxidants enzymes, such glutathione peroxidase and SOD have been described in MDD patients (Maes et al, ; Stefanescu and Ciobica, ). Furthermore, Talarowska et al () showed a decrease in manganese superoxide dismutase gene expression and total protein in recurrent MDD patients. The serum of MDD patients also has an increase of the lipid peroxidation marker MDA (Stefanescu and Ciobica, ).The brain uses a large amount of oxygen, thus this tissue is more vulnerable to oxidative damage (Talarowska et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced levels of antioxidants enzymes, such glutathione peroxidase and SOD have been described in MDD patients (Maes et al, ; Stefanescu and Ciobica, ). Furthermore, Talarowska et al () showed a decrease in manganese superoxide dismutase gene expression and total protein in recurrent MDD patients. The serum of MDD patients also has an increase of the lipid peroxidation marker MDA (Stefanescu and Ciobica, ).The brain uses a large amount of oxygen, thus this tissue is more vulnerable to oxidative damage (Talarowska et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These tests were preceded by a determination of serum total protein. Two measurement techniques were employed [ 19 ]. For the quantitative detection of serum SOD2 protein levels, a commercial kit, NWLSSTM MnSOD ELISA, was used (Northwest Life Science Specialties LLC, Vancouver, Wash., USA).…”
Section: Methodsmentioning
confidence: 99%
“…For the quantitative detection of serum SOD2 protein levels, a commercial kit, NWLSSTM MnSOD ELISA, was used (Northwest Life Science Specialties LLC, Vancouver, Wash., USA). The human MnSOD and GADPH expression the peripheral blood lymphocytes was quantified by real-time PCR using ABI Prism 7000 Sequence Detection System (Applied Biosystems, Foster City, Calif., USA) according to the manufacturer’s protocol [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, this is the first study to systematically investigate the roles of peripheral gene expression for indicators of inflammation and ox-idative balance in personality traits predisposing to a depressive episode. In our previous papers we referred to oxidative and antioxidative imbalances and immune system disorders in patients with symptoms of depression and among healthy people: MnSOD [24], MPO [25], COX-2 [26], iNOS [27], MMP-2 and MMP-9 [28]. At this point, we would like to summarise the correlations related to the functioning of the immune and emotional systems.…”
Section: Discussionmentioning
confidence: 99%